Calcareous nannofossil records and the migration of the Agulhas Return Current during the last 40 kyr - Yu, Chonghan; Su, Xin; Ding, Xuan; Zhang, Jie; Tao, Chunhui; Lv, Shihui (Frontiers in Earth Science, 2024)
The Agulhas Return Current (ARC) transports warm tropical and subtropical waters eastward into the southern Indian Ocean. It plays a crucial role in the oceanographic connections between the Indian, Atlantic, and Southern Oceans. Modern oceanographic observations show that the latitudinal position of ARC varies interannually. However, its historical positional variations remain poorly understood. Calcareous nannofossils can be a good indicator of ancient current migration, though the record of it in the Southwest Indian Ocean is poorly studied. This research aims to understand the characteristics and downcore variation of the calcareous nannofossil assemblages and to trace the record of the ancient ARC. To achieve these goals, this study analyzed pelagic sediments of multicore 34IV-SWIR-S021MC03, 34IV-SWIR-S032MC04, and 34IV-SWIR-S040MC05 from the Southwest Indian Ocean. A total of 13 nannofossil species are identified. The assemblages belong to the subtropical convergence zone regime. They are characterized by warm and cold water species, dominated by E. huxleyi, C. leptoporus, G. muellerae, and F. profunda. According to the AMS 14 C age model and phytoplankton ecological signatures, this study establishes a calcareous nannofossil indicator to trace the migration of the ancient ARC during the last 40 kyr. The result shows three periods of migration: 40-22 kyr, the ancient ARC was in the far north and was moving southwards; 22-14 kyr, a transitional period, the ancient ARC was moving northwards; 14-3 kyr, the ARC is moving southwards. This further suggests that migration of the ancient ARC is more complex than the two recognized phases, and there were essential turning points around the last glacial maximum period. It also acknowledges that the ancient ARC is sensitive to interglacial periods and can be influenced simultaneously by the Southern Hemisphere monsoon and westerly winds.